Balancing water demand for the Heihe River Basin in Northwest China. (October 2017) - Wu, Feng; Bai, Yuping; Zhang, Yali; Li, Zhihui
Abstract: Water crisis becomes the most serious threat to global economic sustainable development. Balancing water demand under the pressure of economic development is a new challenge faced by water resource managers. In this study, we investigated the mutual feedback mechanism between economic systems and eco-hydrological processes in the Heihe River Basin of China with a Water Economic Model (WEM). The WEM is built based on input-output table that embeds water-land resource factors and focuses on the interactive route between water resource and economic elements. On one hand, we investigated the routes and patterns of how eco-hydrological processes acted on economic systems in the upstream of Heihe River Basin, and analyzed how climate change disturbed the economic systems through its impacts on water yield. On the other hand, we explored the feedback of economic systems on eco-hydrological processes through land use interface. We determined the key parameters of simulation and designed the economic development scenarios for the Heihe River Basin. Based on the WEM, we simulated the change of water demand under urbanization and industrial transformation scenarios, supporting scientific basis for the water resource management and policy. Highlights: We built a Water Economic Model (WEM). We compiled the input-output tables of embedded water and land resource factors. The study simulated the balance for water demand in socioeconomic system.